2020
DOI: 10.1016/j.jwb.2019.101026
|View full text |Cite
|
Sign up to set email alerts
|

Which regions matter for MNEs? The role of regional and firm level differences

Abstract: This paper explores the impact of regional and firm level heterogeneity on MNE performance from an operational perspective. We find that the underlying economic growth of a region and the MNE's overall product diversity significantly impact returns from downstream operations in specific regions.Based on a 10 year panel dataset of 1249 US based MNEs, results show that the incremental impact of the degree and speed of operations within a given region, is greater for regions exhibiting faster economic growth than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…In other words, these studies take a macro perspective in analyzing the role of COVID-19 in determining the fluctuations in economies. However, extant research found that the incremental impact of the degree and speed of operations within a given region, is greater for regions exhibiting faster economic growth than others exhibiting slower growth (Demirbag, Glaister, and Sengupta 2019). This means the impact of COVID-19 on corporate performance has obvious regional heterogeneity, since the growth rate is different across regions.…”
Section: Pandemic Impact In the Regional Dimensionmentioning
confidence: 99%
“…In other words, these studies take a macro perspective in analyzing the role of COVID-19 in determining the fluctuations in economies. However, extant research found that the incremental impact of the degree and speed of operations within a given region, is greater for regions exhibiting faster economic growth than others exhibiting slower growth (Demirbag, Glaister, and Sengupta 2019). This means the impact of COVID-19 on corporate performance has obvious regional heterogeneity, since the growth rate is different across regions.…”
Section: Pandemic Impact In the Regional Dimensionmentioning
confidence: 99%
“…Indeed, only a limited number of studies have analyzed detailed and representative data, considering both (a) the large variety of different types of foreign companies and their home country institutions and (b) the profound structural and institutional differences at the local level. Yet, such studies are relevant for economies with highly uneven levels of subnational development (i.e., regional heterogeneity) (Demirbag et al., 2020), which is the case in Brazil (Costa et al., 2018; Ferraz et al., 2020). Moreover, relatively few empirical studies in Latin America have explored the effects of foreign companies on socio‐economic variables, such as education and inequality, that go beyond the traditional focus on productivity and growth (Fajnzylber & Fernandes, 2009; Suanes, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Third, the majority of research on alliance diversity and regional expansion is conducted on large firms from developed countries (Demirbag et al, 2020;Hagedoorn et al, 2018). Scholars highlight that the evidence for firms from large, advanced economies can hardly be applicable to developing market SMEs, which often face significant domestic institutional hardships (Deng & Zhang, 2018;Wu & Deng, 2020).…”
Section: Introductionmentioning
confidence: 99%